ANALYSIS OF SUPPORTING AND INHIBITORY FACTORS OF STUDENT’S LEARNING OUTCOMES SUBJECT OF SCIENCE IN IX GRADE AT AL ISHLAH JUNIOR HIGH SCHOOL IN CILEGON BANTEN PROVINCE - Dewi, Irma Nurmala; Khaeruman, Khaeruman; Noor, Noorsidi Aizuddin Mat (International Journal of Multidisciplinary Research and Literature, 2024)
Teaching and learning activities involve the execution of the curriculum in educational institutions to enable students to attain established objectives. Insufficient student enthusiasm in the educational process significantly affects suboptimal student learning outcomes. This study aimed to analyze the factors that influence teacher strategies in improving the learning outcomes of grade IX students in Sciences Subject at Al-Ishlah Junior High School in Cilegon Banten Province. The research employed a qualitative methodology, utilizing data collection techniques such as observation, interviews, and documentation. The snowball sampling method determined the informants: Subject Teachers, Principals, and Grade IX Students of Al-Ishlah Junior High School. The study results showed that the learning outcomes of Al-Ishlah Junior High School students were quite good, but there were still students who got low learning outcomes. This is evident from the fact that the average daily test scores related to science subjects were entirely satisfactory; however, there were still students whose scores had not yet reached completion. The findings of the study indicate that factors either support or inhibit students' learning outcomes. The internal supporting factors include motivation and attitude, while the external factors include the relationship between parents, teachers, and the environment. Internal inhibiting factors are motivation, intelligence, interests and talents, self-confidence, and discipline. At the same time, external inhibiting factors are the family environment, school environment, and peers. The strategy of science subject teachers in improving student learning outcomes is to provide motivation, varied learning strategies, learning methods appropriate to the situation and condition of students, and optimization of engaging learning media according to the learning material